From Ritual to Resistance: Ṣalawāt al-Ashghīl in the Environmental Struggle of the Wadas Community - Saekhu; Hanik Rosyida; Muhibbin (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2024)
This study examines the significance of ṣalawat ashghil as embodied in the non-violent resistance of the Wadas residents in Purworejo against the construction of the Bener dam. Contrary to the common perception that religion and environmental activism are separate spheres, the people of Wadas demonstrate how religious expression can be closely intertwined with ecological protest. By employing resistance theory and a phenomenological approach, this qualitative research investigates how the recitation of ṣalawat ashghil functions as a form of religious resistance. The findings reveal that this non-violent resistance is deeply rooted in the community’s understanding of the Qur’an and hadīth, embodying what can be described as a lived interpretation of these texts. The villagers attribute spiritual power and protective efficacy to the practice of ṣalawāt ashghīl, viewing it as a means of confronting injustice. Drawing on James C. Scott’s theory of resistance, their actions constitute a subtle yet enduring form of dissent that operates without overt confrontation with dominant power structures. This case offers an alternative framework for understanding Islamic resistance by illustrating how devotional practices can serve as potent vehicles for socio-environmental critique.